APPLICATION OF FLASH CARD LEARNING MEDIA FLAT BUILDING MATERIALS FOR MATHEMATICS SUBJECTS FOR GRADE IV STUDENTS OF SD NEGERI 2 MUARA KATI BARU 1 - povei povei; Agus Triyogo (CV Grasta Glory, 2025)
This study aims to enhance the mathematics learning outcomes of students in flat geometry by applying flashcard learning media in class IV at SD Negeri 2 Muara Kati Baru 1. The background of the study is the low interest in learning and student involvement in mathematics learning, which has an impact on learning outcomes that have not met the Minimum Completion Criteria (KKM). The method used is an experiment with two cycles of action. Each cycle includes one meeting, during which learning outcomes are measured at the end of the activity. The subjects of the study were 16 students, consisting of 8 male students and 8 female students. The instrument used was a learning outcome test. The results of the analysis showed that in cycle I, the average student score was 72 with a completion percentage of 50%, while in cycle II it increased to 85 with completion reaching 85%. Media validation by material, media, and language experts showed a validity level of 89.16% with a very valid category, while the assessment of feasibility by teachers reached 96% (very feasible). The effectiveness of the media was also confirmed through the calculation of a gain score of 0.91, which was categorised as very effective. Based on these findings, the use of flashcard media has been proven to significantly improve student learning outcomes. Further research is suggested to explore the combination of flash cards with digital media or collaborative learning methods to expand the positive impact on student learning outcomes and motivation.